Capote - Clarke, Gerald 1937- (Sony Pictures Home Entertainment, 2006)
In 1959, Truman Capote was a popular writer for The New Yorker. He learns about the horrific and senseless murder of a family of four in Holcomb, Kansas. Inspired by the story, Capote and his partner, Harper Lee, travel to the town to do research for an article. However, as Capote digs deeper into the story, he is inspired to expand the project into what would be his greatest work, "In Cold Blood." He arranges extensive interviews with the convicted killers, especially with Perry Smith. However, his feelings of compassion for Perry conflicts with his need for closure for his book which only an execution can provide. That conflict and the mixed motives for both interviewer and subject make for a troubling experience that would produce an literary account that would redefine modern non-fiction.